The translation of mythical elements in game localization ——A case study of League of Legends - Zhou, Qiqi (Nanyang Technological University, 2022)
With the development of the electronic information age, video games have become a common way of entertainment in people's lives. With the continuous development of China's game industry, more and more games are introduced into the Chinese market. In the process of game localization, how to deal with the understanding obstacles caused by cultural differences is a difficult problem. Mythical element is a kind of cultural symbol, and it is often a difficult point in game localization projects. This dissertation takes League of Legends as an example, selects some texts with mythical elements in League of Legends as research objects, and discusses and analyze the processing strategies of localization teams.